From training to action: addressing training needs in environmental education for child-led participation with adult support - Crespo i Torres, Ferran; Novella Cámara, Ana María; Sabariego Puig, Marta (Frontiers in Education, 2025)
IntroductionEnvironmental education is conceived as a critical social practice aiming to foster an knowledgeable, participatory citizenship capable of taking on contemporary ecological and social challenges. However, although different international frameworks define it as a lifelong process of education for participation and action, the participation of children and adolescents and the accompaniment we provide as educators continue to present challenges. This study investigates the barriers and training needs encountered by environmental educators in Catalonia in boosting child and youth participation in their professional practice, in the light of the diversity of educational settings and situations in the field.MethodsA pragmatic participatory approach was adopted in which a group of 10 participants took part in four participatory workshop sessions to inquire, from the standpoint of their concrete situations, into the challenges they faced as educators and in environmental education as a subject, in addition to their training needs for embracing child and youth participation in their practice.ResultsResults revealed multiple challenges: reconnecting children with the urban natural environment; developing the critical and political capacity to address eco-social conflicts; lack of training for encouraging transformative action; and structural issues such as the absence of an established competency framework, professional instability, job insecurity, and bureaucratic rigidity. Also, a number of training needs were identified, including: systematically conceptualizing and recognizing the value of child participation; mastering methodologies to facilitate participatory, empowering support; networking and knowledge of community resources offering tools for the inclusion of all students. Lastly, the results showed that participatory workshops are a useful tool not only for data-gathering, but also for the professional education and development of their participants.DiscussionOur findings reveal a gap between the founding principles of environmental education and actual professional practice, stressing the urgent need for situated, reflexive, dialogic educator training that will strengthen critical competencies, foster children’s agency, and legitimize the environmental educator as a specialized professional capable of combining theoretical knowledge, participatory methodologies, and critical reflection, thereby contributing to an inclusive, transformative eco-social citizenship in which children are included.